Synthesis of organic nanowires for stretchable, flexible and twistable devices - Quek, Esther Kai Lin. (2012)
Organic semiconductor nanowires were fabricated using conjugated polymer — 14H-benzo[4,5]isoquinolino[2,1-a]perimidin-14-one (IPN). UV-vis absorption and photoluminescence spectroscopy were used to determine the orientation of IPN aggregation to determine the feasibility of its potential purpose as nanowires in flexible electronic devices. The self-assembly of IPN nanowires were facilitated using triblock copolymer as the surfactant, which also yielded other organic structures- microrods, nanorods and nanobelts. The morphology of these structures were characterised under Scanning Electron Microscopy (SEM) and Field Emission Scanning Electron Microscopy (FESEM) and analysed using statistical box plots to propose the growth-change mechanisms causing the different morphology obtained. The results show that optimum conditions of ageing time and amount of surfactant solution plays an important role in fabricating nanowires with good size uniformity.